Evaluating the Efficacy of Knowledge-Transfer Interventions on Animal Health Knowledge of Rural Working Equid Owners in Central Ethiopia: A Cluster-Randomized Controlled Trial - Stringer, Andrew P.; Christley, Rob M.; Bell, Catriona E.; Gebreab, Feseha; Tefera, Gebre; Reed, Karen; Trawford, Andrew; Pinchbeck, Gina L. (Frontiers in Veterinary Science, 2018)
The objectives of this study were to evaluate the efficacy of several knowledge-transfer interventions about donkey health, utilising a cluster-randomised controlled trial (c-RCT), on the long-term knowledge change (approximately six months post intervention) of rural Ethiopian villagers. Knowledge transfer interventions included: an audio programme, a village meeting and a diagrammatic hand-out, which were also compared to both a control group, which received no intervention. All interventions addressed identical learning objectives. Thirty-two villages were randomly selected and interventions randomly assigned to blocks of eight villages. All participants in a village received the same intervention, and knowledge levels were assessed by questionnaire administration both pre and post intervention. Data analysis included multilevel linear and logistic regression models (allowing for clustering of individuals within villages) to evaluate the change in knowledge between the different knowledge-transfer interventions, and to look at other factors associated with change in knowledge. A total of 516 randomly selected participants completed pre-intervention questionnaires, 476 undertook a post-dissemination questionnaire approximately six months later, a follow-up response rate of 92%. All interventions significantly improved the overall knowledge score on the post intervention questionnaire compared to the control group, with the diagrammatic hand-out (coefficient (coef) 10.0, S.E. = 0.5) and the village meeting (coef 8.5, S.E = 0.5) having a significantly greater impact than the audio programme (coef 4.0, S.E = 0.5). There were differences in learning across interventions, learning objectives, age and education levels of the participants. Participants with higher levels of formal education had greater knowledge change but this varied across interventions. In conclusion, knowledge of donkey health was substantially increased by a diagrammatic hand-out and the impact of this simple, low-cost intervention should be further evaluated in other communities in low-income countries. This study should assist in the design and development of effective knowledge-transfer materials for adult learning for rural villagers in low-income countries.